2019
DOI: 10.1080/21691401.2019.1617728
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA linc00858 promotes progress of lung cancer through miR-3182/MMP2 axis

Abstract: In previous studies, numerous dysregulated lncRNAs were identified using RNA-sequencing. Lung cancer is the most common malignant tumour worldwide and the second leading cause in cancer. The aim of this study is to investigate the function and mechanism of lincRNA00858 in the lung cancer. RT-PCR was used to detect the expression of lincRNA00858. Proliferation, invasion, and epithelial-mesenchymal transition (EMT) were examined by CCK8, transwell assay and western blot to evaluate the function of linc00858. Dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
(27 reference statements)
1
23
0
Order By: Relevance
“…Numerous studies have shown that microRNAs play a crucial part in regulating cancer cell apoptosis, proliferation, invasion, growth, and metastasis [23][24][25][26][27]. Therefore, we made a further exploration of whether SFTPC downregulation in lung cancer was mediated by microRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that microRNAs play a crucial part in regulating cancer cell apoptosis, proliferation, invasion, growth, and metastasis [23][24][25][26][27]. Therefore, we made a further exploration of whether SFTPC downregulation in lung cancer was mediated by microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-629-3p was upregulated in LUAD and a potential negative regulator to SFTPC MicroRNAs, a type of endogenous small molecule non-coding single-stranded RNAs, display a repressive effect on target gene expression or mRNA degradation [23,24]. Mountains of evidence show that microRNAs play crucial parts in regulating malignant cell apoptosis, proliferation, invasion, growth and metastasis [23][24][25][26][27]. Herein, we explored whether SFTPC expression was modulated by microRNAs in lung cancer.…”
Section: Sftpc Regulated Luad Cell Proliferation In Vitro and Tumour mentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNA has been showed to play important roles in various disease [17]. For example, Long noncoding RNA LINC00511 contributes to breast cancer tumourigenesis and stemness by inducing the miR-185-3p/E2F1/Nanog axis [18].…”
Section: Discussionmentioning
confidence: 99%
“…LINC00858, a member of the lncRNA family with 2,685 nucleotides in length, was only recently begun to be investigated. Previous studies have indicated that LINC00858 has roles in several tumor types, including lung cancer (7), colorectal cancer (8) and osteosarcoma (9). To the best of our knowledge, LINC00858 has not been previously investigated in RB.…”
Section: Introductionmentioning
confidence: 94%